2024
DOI: 10.1002/cbf.3912
|View full text |Cite
|
Sign up to set email alerts
|

FNDC5/Irisin protects neurons through Caspase3 and Bax pathways

Qiu‐Xia Zhang,
Lin‐Jie Zhang,
Ning Zhao
et al.

Abstract: Irisin is a glycosylated protein formed from the hydrolysis of fibronectin type III domain‐containing protein 5 (FNDC5). Recent studies have demonstrated that FNDC5/Irisin is involved in the regulation of glucose and lipid metabolism, it can inhibit inflammation and have neuroprotective effects. However, the effect and mechanism of FNDC5/Irisin on motor neuron‐like cell lines (NSC‐34) have not been reported. In this study, we used lipopolysaccharide to construct cellular oxidative stress injury models and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The positive effect of irisin on cell viability under AP induction was thwarted by the specific PPARγ antagonist G3335 ( Figure 5 F), further indicating that the activation of PPARγ, possibly via the PPARγ-PGC1α-FNDC5 pathway, is related to the improvement in cell viability under exogenous irisin supplementation. A few studies reported irisin beneficial effect on apoptotic status in several cells, including endocrine pancreas cells [ 53 , 85 , 86 ]. The positive effect of irisin on the cellular viability observed in our study ( Figure 5 F–G) might be downstream of the PPARγ-PGC1α-FNDC5 pathway, due to the modulation of pro- and anti-apoptotic markers activated under stress conditions in favor of pro-survival agents.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of irisin on cell viability under AP induction was thwarted by the specific PPARγ antagonist G3335 ( Figure 5 F), further indicating that the activation of PPARγ, possibly via the PPARγ-PGC1α-FNDC5 pathway, is related to the improvement in cell viability under exogenous irisin supplementation. A few studies reported irisin beneficial effect on apoptotic status in several cells, including endocrine pancreas cells [ 53 , 85 , 86 ]. The positive effect of irisin on the cellular viability observed in our study ( Figure 5 F–G) might be downstream of the PPARγ-PGC1α-FNDC5 pathway, due to the modulation of pro- and anti-apoptotic markers activated under stress conditions in favor of pro-survival agents.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 (CASP3), a cytoplasmic protease, plays a crucial role in apoptosis [58]. Research has shown that CASP3 is involved in the cleavage of β-amyloid protein, as well as Tau protein and presenilin protein (PS1, PS2), which are closely associated with AD [59].…”
Section: Molecular Dynamics Simulation Of the Casp3-6-gingerol Complexmentioning
confidence: 99%
“…The MMP2-6-Gingerol complex exhibited stable hydrogen bonds (1-4) throughout the MD simulation, with a maximum of six hydrogen bonds (Figure 9D). These hydrogen Caspase-3 (CASP3), a cytoplasmic protease, plays a crucial role in apoptosis [58]. Research has shown that CASP3 is involved in the cleavage of β-amyloid protein, as well as Tau protein and presenilin protein (PS1, PS2), which are closely associated with AD [59].…”
Section: Molecular Dynamics Simulation Of the Mmp2-6-gingerol Complexmentioning
confidence: 99%
“…Irisin, by enhancing insulin sensitivity and promoting energy expenditure, could help improve these metabolic issues; 3 , 6 Anti-inflammatory Action, chronic inflammation in individuals with HIV is associated with an increased risk of non-infectious diseases such as cardiovascular and liver diseases. The anti-inflammatory properties of irisin could help mitigate chronic inflammation, thereby reducing the risk of these complications; 7 , 8 Immune Function Modulation, HIV primarily damages the immune system by destroying CD4+ T cells. Irisin might indirectly affect immune regulation and has the potential to improve or support the immune status of individuals with HIV; 5 Promotion of Muscle Function and Reduction of Wasting Symptoms, individuals with HIV may experience muscle wasting and a decline in strength.…”
Section: Irisin Tregs and Aidsmentioning
confidence: 99%
“…Irisin is a glycosylated type I membrane protein, a cleavage product of fibronectin type III domain-containing protein 5 (FNDC5), and is highly homologous between humans and mice. 1–4 Recent studies have shown that irisin plays a significant role under various physiological and pathological conditions, including promoting bone remodeling, 5 improving the prognosis of metabolic diseases, 3 , 6 and exhibiting anti-inflammatory, 7 , 8 anti-oxidative stress, anti-apoptotic, 5 , 6 , 9 neuroprotective, 7 , 10 and organ ischemia-injury protective effects. 9 Multiple studies have indicated that irisin can enhance the function of natural killer cells and play various roles in immune regulation.…”
Section: Introductionmentioning
confidence: 99%